Einstein and the rabbi : searching for the soul - Levy, Naomi (Flatiron Books, 2018)
"A bestselling author and rabbi's profoundly affecting exploration of the meaning and purpose of the soul, inspired by the famous correspondence between Albert Einstein and a grieving rabbi."--